Rare Case Report on Ileal Perforation due to Ingested Mutton Bone - Bhatta, Gakul; Malla, Bala Ram; Rajbhandari, Nripesh (Journal of Karnali Academy of Health Sciences, 2019)
Perforation due to foreign body is not a common cause of surgical emergency. Delay in diagnosis might lead to peritonitis and subsequently sepsis and eventually death. A case with external ileal perforation warrants a wider knowledge sharing for the benefit of medical community. Thus, it makes a important case to be reported.